Enhancing Stakeholders’ Engagement in TVET Policy and Strategy Development in Ethiopia - Tekle, Ashebir; Areaya, Solomon; Habtamu , Getachew (Journal of Technical Education and Training, 2024)
This study investigates the depth of stakeholders’ engagement in the formulation of TVET policies and strategies and assesses the efficacy of awareness-building initiatives in Ethiopia. Anchored in a transformative worldview, this qualitative study utilizes a phenomenological research design and involves 35 participants selected for interviews from 33 organizations, including officials, industry representatives, and TVET deans. Moreover, two separate focus groups comprised of trainers were convened to engage in discussions about the subject matter, and a document analysis was made. The data collection was conducted by the researchers, assisted by a team of five individuals, with one representative from each region. Purposive sampling was employed to select participants. The findings reveal that key stakeholders, specifically the Ministries of Construction, Urban Development, and Tourism, lacked substantive engagement in the policy formulation process. Additionally, some ministerial level and major TVET policy and strategy implementers, like trainers and industries, did not have a clear awareness of the current TVET policy and strategy. Additionally, there is a notable absence of participation from regional agencies, associations, and industries in policy and strategy design. From the total list of 35 interviewed respondents, only 17% were engaged, whereas, from two sets of focus group discussions, none of the stakeholders were engaged in TVET policy and strategy development. The study concludes that Ethiopian TVET policy and strategy formulation suffer from insufficient stakeholders’ involvement and fragmented awareness initiatives. It is inferred that there is an imperative for the Ministry of Labor and Skills to foster awareness and dialogues at both the federal and regional spheres, incorporating feedback from pivotal stakeholders for future policy refinements